An easy and low-cost method of embedding chiral molecules in metal–organic frameworks for enantioseparation. Issue 54 (4th June 2020) - Hu, Xiao-Jing; Huang, Ge; Zhang, Shuo; Fang, Zhi-Bin; Liu, Tian-Fu; Cao, Rong
Abstract : A facile post-synthetic modification method has been demonstrated here to prepare chiral metal–organic frameworks for enantioseparation. Abstract : A facile method, post-synthetic exchange of modulators (PSEm), has been demonstrated here to prepare chiral metal–organic frameworks for enantioseparation. Based on this method, three chiral porous Zr-based metal–organic frameworks have been prepared through exchanging the coordinated modulators on metal clusters of MOFs with commercially available chiral carboxylic acid molecules. In addition, the obtained materials show enantioselectivity toward three different enantiomers, which presents a proof of concept for the design of MOF materials for enantioseparation by an easy and low-cost method.